(untitled) (Journal of Human Sciences, 2021)
The objective of the research is to use multimedia to improve reading abilities in electronic devices, particularly for Arabic learners who are native speakers of other languages. The study group comprises of thirteen male and female students from Petagorsk University in Russia, who are visiting Assiut University. They use the research tools described in the following sections: (List of Reading Skills, Multimedia Software, Teacher’s Guide to Software Use, and Observing an E Note Card). After the results have been acquired, they are subsequently explained and analyzed. The most important of which is that the use of multimedia has an effective impact on developing e-reading skills for learners of Arabic who speak foreign languages, and then and then provide recommendations and suggestions related to the research results.